Polyhydroxyalkanoates Biopolymers Production Strategies - Gahlawat, Geeta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on both production and extraction aspects of Polyhydroxyalkanoates (PHAs) for their commercialization purpose. PHAs have broad range of applications in packaging, food, agriculture and pharmaceutical industries. Until now literature reports have discussed either production strategies or extraction protocols. But for commercialization purpose both issues need to be addressed. This book highlights other copolymers of PHAs which have much better physico-mechanical properties such as elasticity and strength than polyhydroxybutyrate (PHB). Finally efficient product recovery protocols and process optimization strategies including renewable substrates, high cell density cultivations, genetic engineering and mathematical modeling are discussed in detail in order to outline the progress made so far in the area of economic biopolymer production. The primary audience will be scholars, researchers and professors working in colleges, universities, research institutes and government organizations.
Introduction -- Polyhydroxyalkanoates: The Future Bioplastics -- Challenges in PHAs Production at mass scale -- Possible Solutions for commercialization of PHA -- Summary and Future Perspectives.
Keywords: Polymers; Environmental engineering; Biotechnology; Bioremediation; Chemistry, Technical; Polymers; Environmental Engineering/Biotechnology.; Chemical Bioengineering; Industrial Chemistry